SARS‐CoV‐2 nosocomial infection: Real‐world results of environmental surface testing from a large tertiary cancer center. Issue 11 (18th February 2021) - Shah, Mansi R.; Jan, Imraan; Johns, Jeremy; Singh, Kuldip; Kumar, Pallavi; Belarmino, Norma; Saggiomo, Kara J.; Hayes, Carolyn; Washington, Kimyatta; Toppmeyer, Deborah L.; Haffty, Bruce G.; Libutti, Steven K.; et al.
Abstract : BACKGROUND: Despite consensus guidelines, concern about severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) transmission has dissuaded patients with cancer from seeking medical care. Studies have shown that contaminated surfaces may contain viable virus for up to 72 hours in laboratory settings. The purpose of this study was to investigate contamination of SARS‐CoV‐2 on commonly used environmental surfaces in a tertiary cancer care center. METHODS: This study evaluated the incidence of SARS‐CoV‐2 viral RNA in high‐touch outpatient and inpatient cancer center spaces. Surfaces were tested over a 2‐week period after patient or staff exposure but before scheduled disinfection services according to the World Health Organization protocols for coronavirus disease 2019 (COVID‐19) surface sampling. Samples were analyzed via reverse transcriptase–polymerase chain reaction for the presence of SARS‐CoV‐2 RNA. RESULTS: Two hundred four environmental samples were obtained from inpatient and outpatient oncology clinics and infusion suites, and they were categorized as 1) public areas, 2) staff areas, or 3) medical equipment. One hundred thirty surfaces from 2 outpatient hematology and oncology clinics and 36 surfaces from an inpatient leukemia/lymphoma/chimeric antigen receptor T‐cell unit were examined, and all 166 samples were negative for SARS‐CoV‐2. One of 38 samples (2.6%) from COVID‐19+ inpatient units was positive. Altogether, the positive test rate for SARS‐CoV‐2 RNA across all surfaces was 0.5% (1 of 204). CONCLUSIONS: This prospective, systematic quality assurance investigation of real‐world environmental surfaces, performed in inpatient and outpatient hematology/oncology units, revealed overall negligible detection of SARS‐CoV‐2 RNA when strict mitigation strategies against COVID‐19 transmission were instituted. LAY SUMMARY: The potential risks of nosocomial infection with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) have deterred patients with cancer from seeking timely care despite consensus guidelines. This study has found negligible rates of environmental contamination with SARS‐CoV‐2 across a multitude of commonly used surfaces in outpatient and inpatient hematology/oncology settings with adherence to strict infection control protocols. Abstract : There is a low prevalence of surface contamination with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) in outpatient and inpatient hematology and oncology settings where patients with cancer and COVID‐19 are treated. Although surfaces reveal overall negligible detection of SARS‐CoV‐2 RNA, continued studies are needed to monitor rates of virus transmission and the environmental factors involved in the propagation of the SARS‐CoV‐2 infection.